Proteomic Profiling of Ex Vivo Expanded CD34-Positive Haematopoetic Cells Derived from Umbilical Cord Blood - Heiner Falkenberg; Teja Falk Radke; Gesine Kögler; Kai Stühler (Stem Cells International)
Ex vivo expansion of haematopoetic cells by application of specific cytokines is one approach to overcome boundaries in cord blood transplantation due to limited numbers of haematopoetic stem cells. While many protocols describe an effective increase of total cell numbers and the amount of CD34-positive cells, it still remains unclear if and how the procedure actually affects the cells’ properties. In the presented publications, CD34-positive cells were isolated from cord blood and expanded for up to 7 days in media supplemented with stem cell factor (SCF), thrombopoietin (THPO), interleukin 6 (IL-6), and fms-related tyrosine kinase 3 ligand (FLT3lg). At days 3 and 7, expanded cells were harvested and analyzed by flow cytometry and quantitative proteomics. 2970 proteins were identified, whereof proteomic analysis showed 440 proteins significantly changed in abundance during ex vivo expansion. Despite the fact that haematopoetic cells still expressed CD34 on the surface after 3 days, major changes in regard to the protein profile were observed, while further expansion showed less effect on the proteome level. Enrichment analysis of biological processes clearly showed a proteomic change toward a protein biosynthesis phenotype already within the first three days of expression.